Comparing the performance of oversampling techniques in combination with a clustering algorithm for imbalanced learning - Pereira, Mariana Matoso (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence